ChemInform Abstract: A New and Efficient Synthesis of Pyrazole‐Fused Isocoumarins on the Solid Surface of Magnetically Separable Fe3O4@SiO2‐SO3H Nanoparticles. Issue 35 (August 2016) - Mukherjee, Sayan; Kundu, Ashis; Pramanik, Animesh
Abstract: A new procedure enables the synthesis of the title species through condensation of arylhydrazones and ninhydrin under solvent‐free conditions applying sulfonic acid functionalized silica‐coated magnetic nanoparticles.